2008
DOI: 10.1002/adfm.200801197
|View full text |Cite
|
Sign up to set email alerts
|

Ultra Low‐k Films Derived from Hyperbranched Polycarbosilanes (HBPCS)

Abstract: Dense and porous hyperbranched carbosiloxane thin films (HBCSO) are obtained by sol–gel processing using methylene‐bridged hyperbranched polycarbosilanes (HBPCSs) with the general compositional formula {(OMe)2Si(CH2)}. Introduction of porosity is achieved using a porogen templating approach, allowing the control of the films' dielectric constant from 2.9 to as low as 1.8. Over the entire dielectric range, the HBCSO films exhibit exceptional mechanical properties, 2–3 times superior to those obtained for non‐al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 18 publications
0
68
1
Order By: Relevance
“…Recently, it has been demonstrated that the incorporation of alkane bridges in hybrid glasses results in materials with mechanical properties considerably better than glasses containing univalent carbon groups. [6][7][8][9] When organics are incorporated into hybrid glass networks in the form of univalent carbon groups, the molecular connectivity is disrupted and the mechanical properties are signifi cantly degraded. [ 10 ] Thus post-deposition curing to increase the network connectivity by formation of Si-O-Si bonds has been critical to achieve acceptable mechanical properties at the expense of organic component loss, fi lm shrinkage, and degradation of electro-optical performance that accompanies curing.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been demonstrated that the incorporation of alkane bridges in hybrid glasses results in materials with mechanical properties considerably better than glasses containing univalent carbon groups. [6][7][8][9] When organics are incorporated into hybrid glass networks in the form of univalent carbon groups, the molecular connectivity is disrupted and the mechanical properties are signifi cantly degraded. [ 10 ] Thus post-deposition curing to increase the network connectivity by formation of Si-O-Si bonds has been critical to achieve acceptable mechanical properties at the expense of organic component loss, fi lm shrinkage, and degradation of electro-optical performance that accompanies curing.…”
Section: Introductionmentioning
confidence: 99%
“…To further illustrate the unique position of nano-architected materials, Figure 3c compares the hollow alumina nanolattices to several other material systems whose porosity can be varied through processing: hyperbranched poly(amidoamine) conjugated silica (HBPCS) (RD 30-90%), 41 silica xerogel (RD 45-64%), 42 silica aerogel (RD 32-40%), 43 and polyimide aerogel with varying amounts of 2,2-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride (6FDA) in 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 the backbone of the polyimide (0% 6FDA RD 11-16%, 50% 6FDA RD 5.3-8.1%). 28 The dashed contour represents the same scaling as one shown in Figure 3b for nanolattices with relative densities between 1% and 10%.…”
mentioning
confidence: 99%
“…For these reasons, the choice has been limited to simple alkoxysilane molecules containing a carbon bridge between the silicon atoms (Figure 1.6). These hybrid organicinorganic materials are known in the literature under different names: bridged polysilsesquioxanes [161,162], oxycarbosilanes [1,7,[163][164][165] and carbosiloxanes [166]. Similarly to traditional organosilicates, they are stable up to 425-450 °C in an inert atmosphere and incorporation of a certain level of porosity is necessary to achieve k values below 2.4.…”
Section: Hybrid Organic-inorganic: Oxycarbosilanesmentioning
confidence: 99%
“…Another strategy to prepare porous carbon-bridging containing materials was recently developed by Rathore et al [166]. Their approach is based on the sol-gel processing of hyperbranched polycarbosiloxanes (HBPCSO).…”
Section: Hybrid Organic-inorganic: Oxycarbosilanesmentioning
confidence: 99%